2015
DOI: 10.3389/fnins.2015.00178
|View full text |Cite|
|
Sign up to set email alerts
|

Methamphetamine and the hypothalamic-pituitary-adrenal axis

Abstract: Psychostimulants such as methamphetamine (MA) induce significant alterations in the function of the hypothalamic-pituitary-adrenal (HPA) axis. These changes in HPA axis function are associated with altered stress-related behaviors and might contribute to addictive processes such as relapse. In this mini-review we discuss acute and chronic effects of MA (adult and developmental exposure) on the HPA axis, including effects on HPA axis associated genes/proteins, brain regions, and behaviors such as anxiety and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…38 Furthermore, hyperactivity of the hypothalamic-pituitary-adrenal axis has been proposed as a possible mechanism of induction of depression in methamphetamine users. 39 The current study also suggested that reuse of methamphetamine in the follow-up could significantly predict all of the assessed clinical symptoms including manic, depressive, and positive and negative psychotic symptoms. This prediction is much stronger for positive psychotic and manic symptoms but not so strong for depressive and negative psychotic symptoms, in which their respective baseline values are better predictors.…”
Section: Discussionsupporting
confidence: 60%
“…38 Furthermore, hyperactivity of the hypothalamic-pituitary-adrenal axis has been proposed as a possible mechanism of induction of depression in methamphetamine users. 39 The current study also suggested that reuse of methamphetamine in the follow-up could significantly predict all of the assessed clinical symptoms including manic, depressive, and positive and negative psychotic symptoms. This prediction is much stronger for positive psychotic and manic symptoms but not so strong for depressive and negative psychotic symptoms, in which their respective baseline values are better predictors.…”
Section: Discussionsupporting
confidence: 60%
“…Studies in children following prenatal MA exposure in the context of alterations in HPA axis function, find that MA exposure is associated with newborn neurobehavioral patterns of increased stress and cortisol (Smith et al 2008; LaGasse et al 2011; Kirlic et al 2013; Twomey et al 2013; Zuloaga et al 2015). In neonatal rats, MA administration increases CORT release (Schaefer et al 2006, 2008, 2010; Williams et al 2006; Grace et al 2010a, b).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this repeated exposure to high levels of glucocorticoids may produce harmful effects on the brain (e.g., cell death, decreased neurogenesis) similar to those induced by chronic stress (Uno et al 1989; Pham et al 2003). These chronic elevations in glucocorticoids may also be linked to behavioral modifications reported following chronic MA exposure, including altered anxiety- and depression-related behaviors (Nawata et al 2012; Jang et al 2013; London et al 2004; Zuloaga et al 2015b). …”
Section: Discussionmentioning
confidence: 99%